Why ABC Matters: Lexicography and Literary History - Helgason, Jon (Culture Unbound, 2010)
The purpose of this article is twofold. First, I wish to discuss the origins of The Swedish Academy Dictionary against the backdrop of the social and cultural history of lexicography in 18th and 19th century Europe. Second, to consider material aspects of lexicography – the dictionary as interface – in light of German media scientist Friedrich Kittler’s “media materialism”. Ultimately, both purposes intend to describe how letters and writing have been constructed and arranged through-out the course of history. In Kittler’s view, “the intimization of literature”, that took place during second half of the 18th century, brought about a fundamental change in the way language and text were perceived. However, parallel to this development an institutionalization and disciplining of language and literature took place. The rise of modern society, the nation state, print capitalism and modern science in 18th century Europe necessitated (and were furthered by) a disciplining of language and literature. This era was for these reasons a golden age for lexicographers and scholars whose work focused on the vernacular. In this article the rise of the alphabetically ordered dictionary and the corresponding downfall of the topical dictionary that occurred around 1700 is regarded as a technological threshold. This development is interesting not only within the field of history of lexicography, but arguably also, since information and thought are connected to the basic principles of mediality, this development has bearings on the epistemo-logical revolution of the 18th century witnessed in, among other things, Enlightenment thought and literature.